Improving Code Quality in ROS Packages Using a Temporal Extension of First-Order Logic - Come, David; Brunel, Julien; Doose, David (2018 Second IEEE International Conference on Robotic Computing (IRC), 2018)
Robots are given more and more challenging tasks in domains such as transport and delivery, farming or health. Software is key components for robots, and ROS is a popular open-source middleware for writing robotics applications. Code quality matters a lot because a poorly written software is much more likely to contain bugs and will be harder to maintain over time. Within a code base, finding faulty patterns takes a lot of time and money. We propose a framework to search automatically user-provided faulty code patterns. This framework is based on FO++, a temporal extension of first-order logic, and Pangolin, a verification engine for C++ programs. We formalized with FO++ five faulty patterns related to ROS and embedded systems. We analyzed with Pangolin 25 ROS packages looking for occurrences of these patterns and found a total of 218 defects. To prevent the faulty patterns from arising in new ROS packages, we propose a design pattern, and we show how Pangolin can be used to enforce it.